Effect of the α-substituted chiral side chain on the helical conformation of N-substituted poly(p-benzamide). (3rd January 2018) - Yokoyama, Akihiro; Saiki, Tomoaki; Masu, Hyuma; Azumaya, Isao; Yokozawa, Tsutomu
Abstract: The effect of the side chain chiral center position on the secondary structure of oligomers and polymers of N -substituted 4-aminobenzoic acid was studied. Monomer 1 was prepared from l -alanine methyl ester hydrochloride in seven steps. The poly( p -benzamide) having an α-substituted side chain at the nitrogen atom (α-Me-PA ) was obtained from the polymerization of 1 with triethylsilane, CsF, and 18-crown-6 in THF. The circular dichroism (CD) studies in solution demonstrated that α-Me-PA adopted a right-handed helical conformation in protic polar solvents, such as water and methanol, and a random structure in chloroform, indicating that solvophobic interactions played an important role in the helical folding of α-Me-PA . The tetramer of ( S )-4-( sec -butylamino)benzoic acid was synthesized as a model compound of α-Me-PA . The single crystal X-ray analysis of the tetramer revealed that the right- and left-handed helical molecules existed in a one-to-one ratio in the crystal, and that the screw pitch of the right-handed helix was shorter than the left-handed helix. Graphical abstract: Image 1 Highlights: Synthesis of poly( p -benzamide) having α-substituted side chain was investigated. Conformation of the polymer in solution was studied by means of CD spectroscopy. The polymer adopted a helical conformation with the aid of solvophobic interaction. Single crystal X-ray analysis of the model compound was carried out.